Batitude! - Cook, Julia (Nebraska : Boystown, 2015)
Noodle thinks his life just stinks! Homework stinks. Practice stinks. And family pictures - they REALLY stink. Norman David Edwards (Noodle) is having a series of rough days. And Noodle's attitude, or 'baditude' is alienating everyone around him. Luckily, Noodle's mom and teacher are there to help him understand how his bad attitude, or baditude is affecting his mood and those around him. Even his friends are starting to avoid him! If only he can stop looking at everything so negatively, maybe he can turn his frown into a smile. Follow along as Noodle learns how to turn his 'have tos' into 'get tos' and his baditude into gratitude! Tips for educators and parents are also included to help turn your child's attitude around.
Keywords: Children -- Life skills guides -- Juvenile fiction. -- Attitude change in children -- Juvenile fiction. -- Change (Psychology) -- Juvenile fiction